Stenting for carotid artery stenosis - Kern, Rolf; Ringleb, Peter A.; Hacke, Werner; Hennerici, Michael G. (Nature Clinical Practice. Neurology, 2007)
Stenting has increasingly been used for the treatment of carotid artery stenosis, although it is still unknown whether it is as safe and successful as carotid endarterectomy. Several studies have been published, and the preliminary results have been variable, with evidence both in favor of and against this procedure. In the past few months, primary outcome data have been published from two large European randomized multicenter trials (SPACE and EVA-3S). So far, both of these trials have evaluated whether carotid stenting shows noninferiority compared with carotid endarterectomy in symptomatic patients with severe carotid disease over a period of 30 days after intervention. In this Review, we summarize current knowledge on effectiveness of both procedures, and provide an updated meta-analysis based on randomized trial data, including SPACE and EVA-3S. This meta-analysis shows a lower procedure-related rate of stroke or death in surgically treated patients. The long-term risk/benefit ratio of carotid stenting remains to be determined. Two other randomized multicenter trials-ICSS and CREST-are ongoing. With an intended sample size of up to 7,000 patients, future meta-analyses will allow more-accurate treatment recommendations and subgroup analysis.
Gesehen am 09.12.2014